Locating graves in different soil types and burial ages in Pulau Pinang using ground penetrating radar - Iffah Zalikha Roslan,; Muhamad Hafizuddin Mohd Mansor,; Najmiah Rosli,; Nabilah Husna Abdullah Sanusi,; Nur Azwin Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ground-penetration radar (GPR) is a geophysical tool widely applied in archaeological and forensic research, such as identifying the exact position of graves. A detailed GPR survey was conducted on the cemeteries in Permatang Pasir and Titi Teras, Penang Island. Moving a 500 MHz GPR antenna along parallel transects inside grids was used to collect data. The study’s aim was to present two case studies with varying soil types and burial ages. Analysis of reflection shape, reflection strength and signal polarity helped in the interpretation of burial anomalies. The results varied depending on the soil type; in the sandy field, the GPR investigations were clearer and less complicated than in the clayey sand field. When the conditions are ideal (low conductivity areas with little vegetation), GPR provides highly informative and precise results. Time-slices representations were used as a method to provide details about the subsurface reflection at a certain depth.